An evaluative study on mobile crowdsourcing applications for crime watch - Ariffin I.; Solemon B.; Wan Abu Bakar W.M.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Crime; Disaster prevention; Mobile computing; Mobile telecommunication systems; Crowdsourcing; Health monitoring; Information sharing; Local authorities; Mobile applications; Mobile crowdsourcing; Physical locations; Technological revolution; Information dissemination